2014
DOI: 10.5539/ibr.v7n7p10
|View full text |Cite
|
Sign up to set email alerts
|

Can Disclosure Quality Explain Dividend Payouts?

Abstract: This study investigates how a firm's disclosure quality affects its dividend policy. Using a sample of Canadian firms with disclosure data from The Globe and Mail, we empirically test the outcome hypothesis and the substitution hypothesis. The outcome hypothesis posits that dividends are an outcome of an effective governance regime and complements other governance mechanisms while the substitution hypothesis argues that dividend payout is a substitute for other forms of governance. Since disclosure quality can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 54 publications
1
7
0
Order By: Relevance
“…Previous research in developed countries like the US, the UK and Canada, where investor protection is strong, has established a direct positive relationship between disclosure quality and dividend payouts (La Porta et al, 2000, Healy andPalepu, 2001;DeAngelo et al, 2006;Adjaoud and Ben-Amar, 2010). Studies by Kowalewski et al (2008), Lin, Kuo and Wang (2014) and Lin, Kuo and Wang (2016) have also confirmed that a higher level of corporate governance practices in an environment with greater transparent disclosure would result in higher dividend payouts. In countries where investor protection is strong, insiders find it much more difficult to exploit outsiders when asset values, liabilities, and operating performance are reported in a transparent disclosure environment.…”
Section: Introductionmentioning
confidence: 86%
See 4 more Smart Citations
“…Previous research in developed countries like the US, the UK and Canada, where investor protection is strong, has established a direct positive relationship between disclosure quality and dividend payouts (La Porta et al, 2000, Healy andPalepu, 2001;DeAngelo et al, 2006;Adjaoud and Ben-Amar, 2010). Studies by Kowalewski et al (2008), Lin, Kuo and Wang (2014) and Lin, Kuo and Wang (2016) have also confirmed that a higher level of corporate governance practices in an environment with greater transparent disclosure would result in higher dividend payouts. In countries where investor protection is strong, insiders find it much more difficult to exploit outsiders when asset values, liabilities, and operating performance are reported in a transparent disclosure environment.…”
Section: Introductionmentioning
confidence: 86%
“…A number of studies, including Al-Malkawi (2008), Osman & Mohammed (2010), and Al-Ajmi & Abo Hussain (2011) have used panel data because it provides "more informative data, more variability, less collinearity among the variables, more degrees of freedom and more efficiency" (Baltagi, 2001, p.6). Similar to the argument made by Osman & Mohammed (2010), and Lin et al (2014), this study includes both dividend paying firms and non-dividend paying firms to avoid selection bias. Deshmukh (2003) highlights that the exclusion of non-dividend paying firms from any empirical analysis may result in biased and inconsistent estimates of the underlying parameters.…”
Section: Datamentioning
confidence: 99%
See 3 more Smart Citations